Nurses in expanded roles to strengthen community-based health promotion and chronic care: policy implications from an international perspective; A commentary - Claudia B. Maier; Hannah Budde; James Buchan (BMC, 2018)
Abstract Chronic conditions and health inequalities are increasing worldwide. Against this backdrop, several countries, including Israel, have expanded the roles of nurses as one measure to strengthen the primary care workforce. In Israel, community nurses work in expanded roles with increased responsibilities for patients with chronic conditions. They also work increasingly in the field of health promotion and disease prevention. Common barriers to role change in Israel are mirrored by other countries. Barriers include legal and financial restrictions, resistance by professional associations, inflexible labor markets and lack of resources. Policies should be revisited and aligned across education, financing and labor markets, to enable nurses to practice in the expanded roles. Financial incentives can accelerate the uptake of new, expanded roles so that all patients including vulnerable population groups, benefit from equitable and patient-centered service delivery in the communities.